Acmeological center in university educational space - Diana V. Zhuinа (Высшее образование в России)
The article reveals the experience of the Centre for Innovation communities «Mordovia base center of teacher education» – Acmeological center for the organization and the practical implementation of the process of professional and personal development of the subjects of educational environment at pedagogical university. The designed and implemented in the educational process acmeologic model of education is described. Special attention is focused on applied acmeologic pedagogical technologies for the effective formation of teacher’s careercompetencies required in new economic and socio-political reality.